Delayed Postoperative Hematoma Formation after Inflatable Penile Prosthesis Implantation. (28th October 2014) - Garber, Bruce B.; Bickell, Michael
Abstract Introduction Infrequent but serious postoperative complications following inflatable penile prosthesis (IPP) insertion include infection, malfunction, and bleeding. Although prior publications report methods to reduce immediate postoperative bleeding, there is little in the literature concerning the etiology, diagnosis, imaging, and management of delayed bleeding after IPP insertion. Aim The aim of the study was to review cases of delayed postoperative bleeding following IPP insertion in a large single‐surgeon series. Methods We carried out a retrospective chart review of 600 patients implanted with a Coloplast Titan IPP with One‐Touch Release pump by a single surgeon, and analyzed cases of delayed postoperative bleeding. Main Outcome Measure The main outcome measure was an analysis of the incidence, causes, diagnostic methods, treatment, and final outcome of these cases. Results Three out of 600 consecutive patients (0.5%) developed a delayed (defined as >5 days postoperative) hematoma following IPP insertion. All patients presented postoperatively with a swollen surgical site, and all were evaluated with a pelvic computed tomography scan to completely define the extent of the hematoma. Two patients developed a delayed hematoma because of excessive physical activity; the remaining patient bled because of premature administration of enoxaparin sodium (Lovenox) by his cardiologist. All three patients were successfully treated with hospital admission, intravenous antibiotics, wound exploration, hematoma evacuation, and antibiotic washout. All three IPPs were successfully salvaged; none developed peri‐prosthetic infection. Conclusions The incidence of delayed postoperative hematoma following IPP surgery was 0.5% in our series of 600 cases. All cases were successfully managed with intravenous antibiotics, hematoma evacuation, and antibiotic washout. Because of the low incidence of this complication, definitive statements concerning prevention and management cannot be made. However, we now recommend avoiding postoperative anticoagulants for at least 5 days if possible, and avoiding vigorous physical activity for at least 3 weeks. Garber BB and Bickell M. Delayed postoperative hematoma formation after inflatable penile prosthesis implantation. J Sex Med 2015;12:265–269.